Alternative assessment to reduce negative backwash effect: exploring the aspects hindering the successful implementation of alternative assessments - Tahsin, Anika (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Master of Arts in English, 2024.